Living in the Void Between Hearing Health Care Encounters: Evaluation of the Barriers Families Face. - Richlin, Blair C.; Blaiser, Kristina M.; Bush, Matthew (Perspectives of the ASHA Special Interest Groups, 2024)
Purpose: There is a clear need for speech-language pathologists, audiologists, and related health care professionals to understand the barriers to hearing health care, so that we may propose possible solutions. Through interview, collaboration, and analysis, the objective was to identify opportunities to enhance support provided for these children. Method: The authors conducted a review of available literature related to hearing health care disparities. Dr. Matthew Bush, an expert in hearing health care disparities and advocacy, was interviewed on October 12, 2022. Data were extracted and compiled from available literature and the interview including demographics, themes, and available interventions. Results: The section "Entry Barriers" describes findings in the main categories of Steps, Proximity, Health Care Literacy, and Systemic Inequalities. The "Opportunities for Change" section describes topics from the interview for ongoing discussion in the field. Conclusions: Ultimately, having this conversation led exactly in a direction that it should--toward further professional development, awareness, and a call to action. To facilitate meaningful change, we are tasked with active discussion, questioning, probing, and improvement. Only through evolution of existing systemic bias and harmful structures can we make meaningful change.